(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2024)
We live in a world where technology is constantly changing and upgrading, so this change gave birth to artificial intelligence (AI). When intelligence is shown by humans it’s called human intelligence, but when machines show such intelligence it’s called artificial intelligence. And by this constant change in technology we have opened doors to some new threats and humans are incapable to measure and predict such dangers. But on the other hand, AI in today’s era has reached such potential that it can be used to monitor and predict many dangers. This paper presents a technique about how we can use artificial intelligence to monitor traffic in highways, roads streets and in many places where we cannot put traffic signals, and how we can monitor activity of each and every individual vehicle to make world safer for humans and other life forms so we can live in harmony and unison.